Effects of Market Reforms and External Shocks on Indian Stock Indices: Evidence on Structural Breaks and Weak-Form Efficiency - Chattopadhyay, Somnath; Bose, Suchismita (Journal of Reviews on Global Economics, 2017)
This study explores stock market efficiency in India after allowing for potential structural changes induced by reforms processes and/or external shocks. The endogenous determination of structural break dates, using mostly Clemente, Montanes, & Reyes (1998) (CMR) methodology, allows us to identify important events in this respect. External shocks such as occasional stock market scams, policy and political regime changes, oil price shocks and the effect of global market meltdowns have caused abrupt or one time changes in the series mean (additive outlier model), while the reforms processes stand out to be the single most important cause for the gradual shifts in the level of stock indices (innovation outlier model). This underlines the importance of institution building and the domestic policy stance in countering external shocks.